Aktivitas Antibakteri Ekstrak Etanol Daun Pandan Wangi (Pandanus Amaryllifolius Roxb. Ex Lindl) Terhadap Staphyloccocus Aureus Dan Pseudomonas aeruginosa - Yulli Kartika, Eka (Journal of Chemistry Sciences and Education, 2024)
Pandanus amaryllifolius Roxb. Ex Lindl is often found in Indonesia and has antibacterial properties. The secondary metabolite content in Pandanus amaryllifolius leaves is flavonoids, alkaloids, tannins, and steroids, which have antibacterial potential. The aim of this research was to determine the antibacterial activity of the ethanol extract of Pandanus amaryllifolius leaves against the bacteria Staphilaccocus aureus and Pseudomonas aeruginosa. The extraction method in this research used the maceration method using a 96% ethanol solvent. The macerate was concentrated using a vacuum rotary evaporator, and the extract was tested for phytochemistry and antibacterial activity. The antibacterial activity test was measured using the disc diffusion method in various concentrations, namely 20%, 40%, and 60%. The results showed that at a concentration of 60%, the average diameter of the inhibitory area for Staphilaccocus aureus and Pseudomonas aeruginosa bacteria was 1.25 and 1.35 mm, respectively.